Therapeutic value of continuous veno-venous hemofiltration administration in treating fulminant myocarditis. (12th October 2011) - Ma, Min; Hui, Jie; Lv, Baining; Meng, Yanqiu
Abstract : Objective: To evaluate the therapeutic effects of continuous veno-venous hemofiltration (CVVH) in treating fulminant myocarditis (FM). Methods and results: We retrospectively analysed 8 cases of FM patients in our institution from March 2009 to December 2011 and reviewed our experience in treating them with CVVH. Using the paired t test, we compared the following clinical variables between prior to and post CVVH: patient's vital signs, serum chemistry, cardiac enzyme profile, ECG, echocardiography, critical conditions, special treatments including intra-aortic balloon pump (IABP) and pacemaker, and hemofiltration parameters including initiation time, filtration speed and volume and sustaining time. Furthermore, we summarised the clinical and hemofiltration parameters of the deceased patients and compared to survivors. We found CVVH treatment significantly ameliorated patients' condition with most of the studied clinical variables skewing within a normal range. In addition, the application of CVVH was started earlier and sustained longer in survivors than those who died. Conclusion: Early and prolonged use of CVVH is associated with increased survival rate in FM. CVVH is a potential choice of treatment for FM when other supportive treatment is not available and should be used early and sustained for at least 40 h.